A Review Of Potential Anticancers From Antimicrobial Peptides - Khamsah Suryati, Mohd; Saravanan, Dharmaraj; Mohammed Al-Kassim, Hassan (2015)
Cancer is one of the leading causes of morbidity and mortality globally. The drawbacks of conventional chemotherapy such as resistance, lack of specificity, severe toxicity warrant the need to explore alternative approach for the treatment of cancer. Antimicrobial peptides are part of the innate defense mechanism of all organisms and have been developed as potential alternatives in combatting infectious diseases. In addition, anticancer effects of many peptides have been reported with remarkable prospects in some in vitro studies especially on breast, cervical and lung cancer cell lines, and in vivo murine tumour xenografts. This review summarizes the reports on the activities of some selected anticancer peptides on various cancer cell lines.